Vegetable Grafting as a Tool to Improve Drought Resistance and Water Use Efficiency - Kumar, Pradeep; Rouphael, Youssef; Cardarelli, Mariateresa; Colla, Giuseppe (Frontiers in Plant Science, 2017)
Drought is one of the most prevalent limiting factors causing considerable losses in crop productivity, inflicting economic as well as nutritional insecurity. One of the greatest challenges faced by the scientific community in the next few years is to minimize the yield losses caused by drought. Drought resistance is a complex quantitative trait controlled by many genes. Thus, introgression of drought resistance traits into high yielding genotypes has been a challenge to plant breeders. Vegetable grafting using rootstocks has emerged as a rapid tool in tailoring plants to better adapt to suboptimal growing conditions. This has induced changes in shoot physiology. Grafting applications have expanded mainly in Solanaceous crops and cucurbits, which are commonly grown in arid and semi-arid areas characterized by long drought periods. The current review gives an overview of the recent scientific literature on root-shoot interaction and rootstock-driven alteration of growth, yield, and fruit quality in grafted vegetable plants under drought stress. Further, we elucidate the drought resistance mechanisms of grafted vegetables at the morpho-physiological, biochemical, and molecular levels.